Effect of chronic obstructive pulmonary disease on airflow motion using computational fluid dynamics - Jagatis, Balaiyah (2013)
Obstructed airway disease Chronic Obstructive Pulmonary Disease ranked as 6th leading cause of death in 1990 and it is projected to become the 4th leading cause of death worldwide by 2030. Chronic Obstructive Pulmonary Disease (COPD) is disease which will narrow the airway progressively. The narrowing is mainly caused by the wall in the bronchi become thick and inflame. The obstructed airway in the lung will alter the behaviour of the airflow. In order to study the effect of obstructive airways, four models of airway are generated based on 5th to 8th generation from 23 generation of Weibel Model. The simulation are carried out using Reynolds number range of 200 to 1400,corresponding to an average height man breathing from quiet to vigorous state. The fully three-dimensional incompressible laminar Navier—Stokes equations are solved using computational fluid dynamics (CFD) solver on unstructured tetrahedral meshes. In this study, a simplified healthy model is used as reference model and other three models are obstructed are generation 6th and 7th.The simulation results shows that the obstructed airways significantly alters the air flow pattern. The air flow rate ratio in the obstructed models are reduced due to the recirculation happens at the obstructed model which prevents air to enter the lower generation. It is found that, as the Reynolds number increase, the pressure drop also increased drastically in obstructed airway. This maybe the reason why COPD patient should breath gently.